Open divide : critical studies on open access - Herb, Ulrich, 1970-; Schöpfel, Joachim, 1957- (Library Juice Press, 2018)
"Provides a critical assessment of the concept and the reality of open access, with a special attention to its impact in the countries of the Global South"--Resumé vydavatele
Keywords: open access; open access -- rozvojové země; vědecká komunikace; pedagogická komunikace; publikační činnost; vědecké informace; dostupnost informací; open access -- developing countries; communication in science; communication in learning and scholarship; publication activity; scientific information; information availability; studie; sborníky; studies; papers of several authors